1992
DOI: 10.1002/jor.1100100216
|View full text |Cite
|
Sign up to set email alerts
|

Tissue ingrowth into titanium and hydroxyapatite‐coated implants during stable and unstable mechanical conditions

Abstract: Summary: Lack of initial mechanical stability of cementless prostheses may be responsible for fibrous tissue fixation of prosthetic components to bone. TO study the influence of micromovements on bony ingrowth into titanium alloy (Ti) and hydroxyapatite (HA)-coated implants, a loaded unstable device producing movements of 500 pm during each gait cycle was developed. Mechanically stable implants served as controls. The implants were inserted into the weight-bearing regions of all four femoral condyles in each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
294
1
10

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 456 publications
(321 citation statements)
references
References 35 publications
(16 reference statements)
11
294
1
10
Order By: Relevance
“…Our previous work with gap implants has consistently shown abundant ongrowth of fibrous tissue, inferior bony ongrowth, and poor mechanical fixation (Soballe et al 1990, Elmengaard et al 2005. In previous studies, the titanium implant surface has been shown to be similar to that of commercially available prostheses with a plasma spray titanium coating (Soballe et al 1992(Soballe et al , 1993. We hypothesized that the combination of TGF-β1 and IGF-1 in PDLLA would enhance the osseointegration and mechanical fixation of unloaded cylindrical porous-coated titanium implants surrounded by a gap.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous work with gap implants has consistently shown abundant ongrowth of fibrous tissue, inferior bony ongrowth, and poor mechanical fixation (Soballe et al 1990, Elmengaard et al 2005. In previous studies, the titanium implant surface has been shown to be similar to that of commercially available prostheses with a plasma spray titanium coating (Soballe et al 1992(Soballe et al , 1993. We hypothesized that the combination of TGF-β1 and IGF-1 in PDLLA would enhance the osseointegration and mechanical fixation of unloaded cylindrical porous-coated titanium implants surrounded by a gap.…”
Section: Discussionmentioning
confidence: 96%
“…Shorter femoral stems, aimed at giving a more physiological load pattern in the proximal femur, have become popular lately because of expectations of reducing stress shielding. Absence of a diaphyseal engaging stem is a key factor to prevent off-loading of the proximal femoral bone, but at the same time it will challenge the primary stability necessary for bone osseointegration of the femoral implant (Søballe et al 1992). …”
mentioning
confidence: 99%
“…Moreover, experimental studies have shown that initial implant stability is essential to bone ingrowth (Cameron et al 1973, Ducheyne et al 1977, Pilliar et al 1986, Søballe et al 1992, Bragdon et al 1996, Jasty et al 1997, Heck et al 1986. It is therefore important to create initial implant stability during surgery so as to ensure the latter stability achieved by bony ingrowth.…”
mentioning
confidence: 99%